(untitled) (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Infertility affects approximately one in every six couples in Bangladesh. While in vitro fertilization (IVF) is a highly successful treatment, comprehensive localized data on factors influencing its outcome is scarce. This study aimed to determine the demographic, clinical, and procedural factors significantly associated with conception following IVF treatment among couples in Dhaka, Bangladesh. Methods: This was a hospital-based cross-sectional analytical study conducted at the HOPE and Lab Aid IVF Clinics in Dhaka between January and December 2024. A total of 126 infertile women (aged 20 to 47 years) undergoing IVF were enrolled. The primary dependent variable was IVF outcome, defined as conception (clinical pregnancy confirmed by ultrasound), while the secondary dependent variable was live-birth. Univariate analysis utilizing independent samples t-tests and Chi-square tests was performed to assess associations between independent variables and the outcome, with a significance level set at p < 0.05. Results: The overall clinical conception rate was 37.3% (47 out of 126 women). Procedural and embryological factors demonstrated the strongest association with success (p < 0.001). Specifically, women who conceived were significantly more likely to have received more than 2 embryos transferred and to have had 3–4 oocytes transferred. Counter-intuitively, conception was also positively associated with increased female age (p = 0.026), age at starting IVF (p = 0.021), and longer duration of infertility (p = 0.021). Factors such as BMI, systemic diseases (hypothyroidism, diabetes mellitus), and the type of infertility were not significantly associated with the outcome. Conclusion: In this clinical setting, procedural factors, particularly the quantity of embryos transferred, are the strongest predictors of IVF success. The unexpected positive association between advanced age or duration of infertility and conception suggests unique selection biases within the local private healthcare system that warrant further, controlled investigation via multivariate analysis. This data is crucial for refining patient counseling and optimizing treatment protocols locally. Ibrahim Cad Med J 2025, 15(1): 37-42